Glutamatergic CYLD deletion leads to aberrant excitatory activity in the basolateral amygdala: association with enhanced cued fear expression - Huidong Li; Faqin Li; Zhaoyi Chen; Erwen Wu; Xiaoxi Dai; Danni Li; Haojie An; Shiyi Zeng; Chunyan Wang; Li Yang; Cheng Long (Neural Regeneration Research)
Neuronal activity, synaptic transmission, and molecular changes in the basolateral amygdala play critical roles in fear memory. Cylindromatosis (CYLD) is a deubiquitinase that negatively regulates the nuclear factor kappa-B pathway. CYLD is well studied in non-neuronal cells, yet under-investigated in the brain, where it is highly expressed. Emerging studies have shown involvement of CYLD in the remodeling of glutamatergic synapses, neuroinflammation, fear memory, and anxiety- and autism-like behaviors. However, the precise role of CYLD in glutamatergic neurons is largely unknown. Here, we first proposed involvement of CYLD in cued fear expression. We next constructed transgenic model mice with specific deletion of Cyld from glutamatergic neurons. Our results show that glutamatergic CYLD deficiency exaggerated the expression of cued fear in only male mice. Further, loss of CYLD in glutamatergic neurons resulted in enhanced neuronal activation, impaired excitatory synaptic transmission, and altered levels of glutamate receptors accompanied by over-activation of microglia in the basolateral amygdala of male mice. Altogether, our study suggests a critical role of glutamatergic CYLD in maintaining normal neuronal, synaptic, and microglial activation. This may contribute, at least in part, to cued fear expression.